Adverse drug reaction - Olawale, Oladoye Oluwole; Kezeli, Tamar; Nikoleishvili, Elza; Sulashvili, Nodar (Caucasus Journal of Health Sciences and Public Health, 2018)
An adverse drug reaction (ADR) is an unwanted, also an undesirable effect of a drug medication that occurs during usual use in the clinic. It is an unintended noxious response which occurs after the normal use of a drug, which is suspected to be associated with the drug. Every drug that can produce the therapeutic effect on the body can also has the ability to produce unwanted side effects. Health professionals should all be well grounded in the knowledge and awareness that these unwanted effects pose to the health care system and very importantly ways to avoid these adverse drug reactions. These adverse drug reactions’ occurrence is almost daily in the institution that provides health care and it can adversely affect a patient’s quality of life, often causing considerable morbidity and mortality. It is said to be responsible for an approximate of 1 in 20 admissions in the hospital. The aim of this study is to briefly discuss some facts about ADR’s and their prevention, and their diagnosis.